POTENSI BANJIR BANDANG MENGGUNAKAN ANALISIS MORFOMETRI DI DAERAH ALIRAN SUNGAI KLAGISON KOTA SORONG - Anif Farida; Mierta Dwangga (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2022)
Flash flood is water level increases rapidly in the river beyond flood level and occurs due to extreme weather. It's happened quickly without warning. The Klagison Watershed in Sorong City has grown rapidly and often had flooded. Settlements dominate almost on watershed areas and there are many hills that are deforested due to mining activities upstream. This study aims to examine the morphometric conditions and to analyze the spatial distribution of the potential flash flood in the Klagison Watershed of Sorong City based on morphometric analysis. GIS is used to obtain morphometric parameters such as linear, relief and aerial parameters. The correlation coefficient between each morphometric parameter was calculated using Pearson Correlation. Determination of potential flash flood areas using the priority zone formula. The result shows that the Klagison watershed has high erosion potential and large runoff based on morphometric analysis. This can be seen in the high value of the texture ratio (T) and low Constant channel maintenance (C) so that the runoff volume is also large. The Lof value in all sub-watersheds is small, which means that surface runoff will quickly to the channel. The flash flood potential in the Klagison watershed is very low (Sub-watershed 1 and Sub-watershed 5), moderate (Sub-watershed 3 and Sub-watershed 4), high (Sub-watershed 2) and very high (Sub-watershed 6 and Sub-watershed 7). It means that Sub-watershed 2, Sub-watershed 6 and Sub-watershed 7 need management priorities related to disaster mitigation. Keywords: flash flood; morphometry; watershed